2020
DOI: 10.1038/s41523-020-0153-3
|View full text |Cite
|
Sign up to set email alerts
|

Clinical development of immunotherapies for HER2+ breast cancer: a review of HER2-directed monoclonal antibodies and beyond

Abstract: Human epidermal growth factor receptor 2-positive (HER2 +) breast cancer accounts for~25% of breast cancer cases. Monoclonal antibodies (mAbs) against HER2 have led to unparalleled clinical benefit for a subset of patients with HER2 + breast cancer. In this narrative review, we summarize advances in the understanding of immune system interactions, examine clinical developments, and suggest rationales for future investigation of immunotherapies for HER2 + breast cancer. Complex interactions have been found betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
107
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(108 citation statements)
references
References 141 publications
(157 reference statements)
0
107
0
1
Order By: Relevance
“…Its therapeutic activity against HER2+ breast carcinoma is being evaluated in phase II trials, but also some authors such as Li et al [101] and Jiang et al [5] have showed its efficacy as a targeted therapy for HER2+ gastric and ovarian cancers, respectively. Other examples of anti-HER2 ADCs whose antiproliferative activity is being evaluated in clinical trials for the treatment of HER2+ cancers are ARX788, TAK-522, A116, Tmab Duocarmizine, ALT-P7, DHE50815A, MEDI4276, and Tmab Deruxtecan [89,99,[102][103][104][105]. More information about them, as well as about SYD98 and Tmab deruxtecan [83], can be found in Table 2.…”
Section: Current and Future Situation Of Trastuzumab-based Nanomedicinementioning
confidence: 99%
See 1 more Smart Citation
“…Its therapeutic activity against HER2+ breast carcinoma is being evaluated in phase II trials, but also some authors such as Li et al [101] and Jiang et al [5] have showed its efficacy as a targeted therapy for HER2+ gastric and ovarian cancers, respectively. Other examples of anti-HER2 ADCs whose antiproliferative activity is being evaluated in clinical trials for the treatment of HER2+ cancers are ARX788, TAK-522, A116, Tmab Duocarmizine, ALT-P7, DHE50815A, MEDI4276, and Tmab Deruxtecan [89,99,[102][103][104][105]. More information about them, as well as about SYD98 and Tmab deruxtecan [83], can be found in Table 2.…”
Section: Current and Future Situation Of Trastuzumab-based Nanomedicinementioning
confidence: 99%
“…[83],2 [89],3 [99],4 [100],5 [104],6 [105]. AF-HPA: auristatin F-hydroxypropylamide; NSCLC: non-small cell lung carcinoma; PBD-MA: pyrrolo[2,1-c][1,4]benzodiazepine monoamide.…”
mentioning
confidence: 99%
“…19 Unlike the other three HERs (HER1, HER3, and HER4), HER2 is highly expressed in many cancer cells, especially in some breast cancers. 20 Moreover, medicines using HER2 as the binding site have been approved by the US FDA for clinical use. 21 Thus, HER2 is considered to be a promising target for theranostic nanomaterials development.…”
Section: Targeting Peptidesmentioning
confidence: 99%
“…Monoclonal antibodies are identical Ig produced by clonal immune cells [96]. Although their antitumoral effect is caused by their binding ability and the inhibition of their corresponding receptor, an additional immunological pathway exists for anti-HER2-targeted monoclonal antibodies by which the adaptive and innate immune systems are activated mainly through the antibody-dependent cell-mediated cytotoxicity of natural killer cells and monocytes against tumor cells [97][98][99][100]. Margetuximab, a novel chimeric anti-HER2 IgG1 antibody [101,102], binds to the same receptor and has anti-proliferative effects similar to those of trastuzumab, but it is intended to have a stronger effect on the immune system due to modification of the Fc region.…”
Section: Anti-her2 Targeted Antibody Therapymentioning
confidence: 99%